Chemical Composition and Biological Activity of Tanacetum balsamita Essential Oils Obtained from Different Plant Organs - Vukic, Milena D.; Vukovic, Nenad L.; Obradovic, Ana D.; Galovičová, Lucia; Čmiková, Natália; Kačániová, Miroslava; Matic, Milos M. (Plants (Basel), 2022)
The aim of this study is to evaluate the chemical composition of Tanacetum balsamita L. essential oils (EOs) obtained from different plant organs, flowers (FEO), leaves (LEO), and stems (SEO), as well as to assess their biological properties. The results obtained by using GC and GC/MS analysis indicate that this plant belongs to the carvone chemotype. Moreover, we examined the oil’s antimicrobial and antitumor potential. Antimicrobial effects were determined using minimum inhibitory concentrations assay and the vapor phase method. Obtained results indicate better antimicrobial activity of investigated EO samples compared to the commercially available antibiotics. On the treatment with FEO, Y. enterocolitica and H. influenzae showed high sensitivity, while treatment with LEO and SEO showed the highest effects against S. aureus. The vapor phase method, as an in situ antibacterial analysis, was performed using LEO. Obtained results showed that this EO has significant activity toward S. pneumoniae in the apple and carrot models, L. monocytogenes in the pear model, and Y. enterocolitica in the white radish model. The potential antitumor mechanisms of FEO, LEO, and SEO were determined by the means of cell viability, redox potential, and migratory capacity in the MDA-MB-231 and MDA-MB-468 cell lines. The results show that these EOs exert antiviability potential in a time- and dose-dependent manner. Moreover, treatments with these EOs decreased the levels of superoxide anion radical and increased the levels of nitric oxide in both tested cell lines. The results regarding total and reduced glutathione revealed, overall, an increase in the levels of total glutathione and a decrease in the levels of reduced glutathione, indicating strong antioxidative potential in tested cancer cells in response to the prooxidative effects of the tested EOs. The tested EOs also exerted a drop in migratory capacity, which indicates that they can be potentially used as chemotherapeutic agents.